Design of a 2D no-flow chamber to monitor hematopoietic stem cells. Issue 1 (23rd October 2014) - Cambier, Théo; Honegger, Thibault; Vanneaux, Valérie; Berthier, Jean; Peyrade, David; Blanchoin, Laurent; Larghero, Jerome; Théry, Manuel
Abstract : We designed a very simple 2D array of chambers protected from flow and supplied by a single inlet in order to easily monitor and stain hematopoietic stem cells over long periods of time. Abstract : Hematopoietic stem cells (HSCs) are the most commonly used cell type in cell-based therapy. However, the investigation of their behavior in vitro has been limited by the difficulty of monitoring these non-adherent cells under classical culture conditions. Indeed, fluid flow moves cells away from the video-recording position and prevents single cell tracking over long periods of time. Here we describe a large array of 2D no-flow chambers allowing the monitoring of single HSCs for several days. The chamber design has been optimized to facilitate manufacturing and routine use. The chip contains a single inlet and 800 chambers. The chamber medium can be renewed by diffusion within a few minutes. This allowed us to stain live human HSCs with fluorescent primary antibodies in order to reveal their stage in the hematopoiesis differentiation pathway. Thus we were able to correlate human HSCs' growth rate, polarization and migration to their differentiation stage.